Amorphous-crystalline attapulgite / carbon composite material as well as preparation method and application thereof

By synthesizing an amorphous layer in situ on the surface of the base carbon to form an amorphous-crystal concave-convex rod/carbon composite material, the complex and energy-consuming problem of amorphous catalyst preparation in the prior art is solved, and the effect of efficient removal of heavy metals and improving catalytic degradation efficiency is achieved.

CN119657082APending Publication Date: 2025-03-21HUNAN AGRI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510025568.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-08
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The prior art has complex and energy-consuming problems in the preparation, design and performance regulation of amorphous catalysts, and lacks a simple and efficient synthesis method.

Method used

By synthesizing an amorphous layer in situ on the surface of the base carbon, an amorphous-crystal concave-convex rod/carbon composite material is formed, and the heavy metal ions are converted into a metal amorphous layer by using the impregnation of metal ions, which is wrapped around the surface of the crystalline layer material.

Benefits of technology

The removal and loading of heavy metal ions in water is achieved, the catalytic effect on organic matter is improved, the electron transfer capacity and degradation efficiency are significantly enhanced, and secondary pollution is avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119657082A_ABST
    Figure CN119657082A_ABST
Patent Text Reader

Abstract

The invention discloses an amorphous-crystalline attapulgite / carbon composite material as well as a preparation method and application thereof. The preparation method comprises the following steps: S1, preparing a preliminary activated composite material; and S2, metal ion impregnation. The surface of the attapulgite / carbon composite material is a metal amorphous layer. The composite material can be used as a catalyst for degrading levofloxacin in a PDS system, the primarily activated material can generate a metal amorphous layer in situ by utilizing inherent pollutants in a water environment to form the attapulgite / carbon composite material with the metal amorphous layer on the surface, and the material has the advantages of high catalytic efficiency and high degradation rate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of catalysts, and more specifically, relates to an amorphous-crystalline metal attapulgite / carbon composite material and a preparation method and application thereof. Background Art

[0002] The latest research results show that materials with amorphous structures have more unsaturated sites, more defects, unique electronic structures, etc. Compared with crystalline catalysts, amorphous catalysts have abundant unsaturated sites, high active site density, large adsorption capacity, and are less restricted by grain boundaries and lattices. Therefore, compared with crystalline materials, their excellent degradation efficiency and catalytic stability are widely favored by researchers.

[0003] However, there are still many scientific problems and challenges in the preparation, design and performance regulation of amorphous catalysts. The methods commonly used to prepare amorphous materials are melt quenching, vapor deposition, ion bombardment, strong laser radiation, high-temperature explosion, hydrogen arc furnace smelting, quartz tube water quenching, copper mold casting: a water-cooled copper mold is set under the heating device, and the amorphous alloy components are melted and then cooled into amorphous by suction casting or other methods, directional zone melting, sputtering, and mechanical alloying. These methods are complex and energy-consuming. Therefore, the development of a simple and efficient method to synthesize amorphous materials has become a hot topic of the times. This patent is dedicated to studying a simple and efficient in-situ synthesis method to synthesize an amorphous layer on the surface of the base carbon, converting the base carbon into an amorphous-crystalline biscuit-type composite material, and providing an application scenario. Summary of the invention

[0004] The purpose of the present invention is to provide an amorphous-crystalline attapulgite / carbon composite material and its preparation method and application, and the heavy metal ions are converted into a metal amorphous layer in situ and wrapped on the surface of the crystalline layer material through the adsorption of heavy metal ions by the composite material. This method can not only remove the heavy metal ions existing in the water itself, but also load them on the surface of the composite material to form an amorphous layer, thereby improving the catalytic effect on organic matter; the in-situ modified material can significantly enhance the ability of electron transfer in the PDS system due to the presence of the metal amorphous layer, greatly improve the degradation efficiency, and will not cause secondary pollution.

[0005] An in-situ preparation method of an amorphous-crystalline attapulgite / carbon composite material comprises the following steps:

[0006] S1. Preparation of a preliminary activated composite material (LAK): industrial alkali lignin and attapulgite are fully mixed in a mass ratio of 2:1-2:7. After being mixed evenly, the mixed material is transferred to a vacuum tube furnace and stabilized under the protection of an inert gas for 10-30 minutes, and then the temperature is increased to 600° C. at a rate of 5-10° C. / min and pyrolyzed for 1-2 hours to obtain a preliminary activated composite material, which is then sieved through a 200-mesh sieve;

[0007] S2. Impregnation of metal ions:

[0008] The plasma composite material obtained in step S1 is immersed in a metal salt solution to obtain an amorphous-crystalline metal-modified attapulgite / carbon composite material.

[0009] Furthermore, in step S1, the pyrolysis temperature is 600°C and the pyrolysis time is 1-2h.

[0010] Furthermore, in step S1, the pyrolysis heating rate is 5°C / min-10°C / min.

[0011] Furthermore, in step S1, the metal salt solution is obtained by dissolving a metal water-soluble salt in water. In the present invention, there is no restriction on its content, as long as the metal ions can be loaded on the attapulgite / carbon composite material to form a crystalline-amorphous composite material. For example, the heavy metal concentration is 150ppm and the immersion time is ≥5min.

[0012] Furthermore, in step S2, the metal ions in the metal salt solution are Cu, or Cu and Cd, or Ni, or Pb.

[0013] The present invention also provides an amorphous-crystalline attapulgite / carbon composite material prepared by the method.

[0014] Furthermore, the present invention also provides the use of the amorphous-crystalline attapulgite / carbon composite material as a catalyst in the activated PDS catalytic degradation of levofloxacin in water.

[0015] In the present invention, the composite material obtained in step S2 can also be directly added as a catalyst to levofloxacin wastewater (eg, chicken farm wastewater) containing metal ions (Cu / Cu-Cd / Ni / Pb).

[0016] Compared with the prior art, the technical solution of the present invention has the following beneficial effects:

[0017] The preparation method of the invention is simple, and the obtained material is in a crystalline / amorphous biscuit shape; the loading of metal ions can improve the catalytic efficiency and greatly increase the removal rate of levofloxacin. In addition, the metal ions and the composite material form an amorphous layer, which can not only firmly adsorb the metal ions on the surface, but also avoid secondary pollution caused by metal ion desorption during the removal of levofloxacin; and the amorphous layer has more unsaturated bonds, which can provide more catalytic sites.

[0018] In addition, since the composite material has an extremely rapid adsorption process for heavy metals, in actual application, the composite material can be directly added to wastewater containing metal ions and levofloxacin, and the wastewater can be treated with PDS. The composite material is used to adsorb and fix the heavy metal ions existing in the water body itself, so that the heavy metal ions cooperate with the composite material to participate in the process of activating PDS to achieve the purpose of efficiently degrading organic matter. It can not only remove heavy metal pollution in water, but also efficiently degrade organic pollutants, providing a new idea for the treatment of water pollutants. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 XRD diagrams of modified attapulgite / carbon composite materials prepared in the examples and comparative examples of the present invention;

[0020] Wherein, a is the XRD diagram of Comparative Example 1-2, and b is the XRD diagram of Example 1-4.

[0021] Figure 2 This is the SEM image of LAK in Example 1.

[0022] Figure 3 These are the SEM and EDS images of LAK-M in Example 1; wherein a is the SEM image after adsorption of Cd and Cu, b is the EDS image of Cd, and c is the EDS image of Cu.

[0023] Figure 4 TEM characterization analysis before and after the formation of the metal amorphous layer;

[0024] Among them, a is the morphology image before adsorption of heavy metals, bc is the high-resolution image before adsorption of heavy metals, d is the electron diffraction image before adsorption of heavy metals, e is the morphology image after adsorption of heavy metals to form a metal amorphous layer, f is the high-resolution image after adsorption of heavy metals to form a metal amorphous layer, and g is the electron diffraction image after adsorption of heavy metals to form a metal amorphous layer.

[0025] Figure 5 Chronoamperometric test (it) results of LAK-M and LAK prepared in Example 1. DETAILED DESCRIPTION

[0026] Many specific details are set forth in the following description to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways than those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited to the specific implementation disclosed below.

[0027] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. It should be noted that the reagents used in the present embodiment are all common commercial products.

[0028] Example 1

[0029] A crystalline-amorphous bimetallic modified attapulgite / carbon composite material, the preparation method of which is as follows:

[0030] Industrial alkali lignin and attapulgite were fully mixed in a mass ratio of 2:1. After mixing evenly, the mixed material was transferred to a vacuum tube furnace and stabilized for 30 minutes under the protection of inert gas. The temperature was increased to 600°C at 10°C / min and pyrolyzed for 2 hours to obtain a preliminary activated composite material (LAK) and then passed through a 200-mesh sieve.

[0031] LAK was immersed in 300 ppm copper nitrate solution and 300 ppm cadmium nitrate solution to obtain a crystalline-amorphous bimetallic modified attapulgite / carbon composite material (LAK-M).

[0032] Example 2

[0033] On the basis of Example 1, LAK was immersed in 50 ppm copper nitrate solution and 50 ppm cadmium nitrate solution to obtain a crystalline-amorphous bimetallic modified attapulgite / carbon composite material (LAK-M-50)

[0034] Example 3

[0035] On the basis of Example 1, LAK was immersed in 200 ppm copper nitrate solution and 200 ppm nickel nitrate solution to obtain a crystalline-amorphous bimetallic modified attapulgite / carbon composite material (LAK-Cu, Ni).

[0036] Example 4

[0037] On the basis of Example 1, LAK was immersed in a 150 ppm copper nitrate solution to obtain an amorphous-crystalline attapulgite / carbon composite material (LAK-Cu).

[0038] Example 5

[0039] On the basis of Example 1, LAK was immersed in 150 ppm copper nitrate and 150 ppm lead nitrate solution to obtain an amorphous-crystalline metal-modified attapulgite / carbon composite material (LAK-Cu, Pb).

[0040] Comparative Example 1

[0041] Based on Example 1, LAK was immersed in a 150ppm cadmium nitrate solution. After only adsorbing heavy metal Cd, it was found that no amorphous layer could be formed on the surface of the attapulgite / carbon composite material. At the same time, degradation experiments in the PDS system found that the removal rate of LEV was only 41%, which proved the important role of the amorphous layer.

[0042] Comparative Example 2

[0043] Based on Example 1, LAK was immersed in a 50ppm lead nitrate solution, and after only heavy metal lead was adsorbed, an amorphous layer could not be formed on the surface. At the same time, degradation experiments were conducted in a PDS system and found that the removal rate of LEV was only 32.15%, which further proved the important role of the amorphous layer.

[0044] Performance Testing

[0045] like Figure 1 As shown, the XRD spectrum shows that the LAK-M material has obvious amorphous diffraction peaks. Most studies have shown that after adsorbing Cd (Ⅱ) and Pb (Ⅱ) in the solution, there are still obvious diffraction peaks. This shows that LAK can purposefully convert Cu, Cu and Cd / Ni into amorphous substances. The LAK-M material after impregnation with metal elements is not a standard amorphous diffraction peak. By comparison, it is found that the diffraction peak with very low intensity that appears after the reaction should be the characteristic peak of the base carbon present in the substance after the reaction. Due to the limited amount of Cu and Cd adsorbed on the surface of the material, the material is not completely covered by the amorphous heavy metal substance, and an uncovered base carbon peak appears. This also preliminarily shows that LAK can purposefully adsorb heavy metals and convert heavy metals into amorphous substances. In Comparative Examples 1 and 2, Cd or Pb is impregnated alone, and Cu is not impregnated, and an amorphous layer cannot be formed. This may be because Cu can quickly combine with the reaction sites on LAK to form an amorphous structure, while the single Cd, Pb, and Ni combine slowly with the reaction sites on LAK to form a crystalline structure.

[0046] like Figure 2 As shown in Figure 1, before impregnation with metal elements, the LAK surface is a short rod-like structure. Figure 3 As shown in the figure, a large amount of flocculent material adheres to the surface of LAK-M material after impregnation with metal elements. Combined with the EDS results, it is proved that Cd and Cu are indeed adsorbed on the surface of the material. This is preliminary evidence that the heavy metals adsorbed on the surface of the material combine with the active sites on the surface of the material to form an amorphous layer wrapped around the surface of the material.

[0047] TEM analysis was performed to verify that LAK can purposefully convert Cu and Cd into amorphous substances after adsorbing Cu and Cd. Figure 4It can be seen that the transmission electron microscope can be used to observe the fine structure of the sample. The TEM comparison of the materials before and after the reaction is helpful to prove that after the material adsorbs heavy metals, a dense amorphous layer can be formed on the surface.

[0048] The conditions for removing levofloxacin by the PDS system are pH = 6, Cu = 300 ppm, Cd = 300 ppm, LEV = 50 ppm, material dosage 0.5 g / L, rotation speed 200 rpm, and temperature 25°C.

[0049] The modified attapulgite / carbon composite material prepared in the examples and comparative examples was added to remove the degraded levofloxacin and then the content of metal elements dissolved in the test solution was tested. The results are shown in Table 1.

[0050] Table 1

[0051]

[0052] As shown in Table 1, the material containing amorphous layer (Example 1) is 81.35% due to the existence of crystalline / amorphous strong interface effect, and the performance of removing levofloxacin of the material (Comparative Example 1) without amorphous layer is 41.00%. This advantageously proves the superiority of amorphous layer material to removing levofloxacin. The existence of amorphous phase in amorphous layer has more randomly oriented unsaturated bonds, which is conducive to the adsorption of reactants. In addition, there are a large number of local structures that can be flexibly changed in the amorphous phase, which can accelerate the charge transfer between active sites and intermediates.

[0053] Figure 5 The electron transfer rate during the PDS activation process was studied by performing a chronoamperometric test (it) on the LAK-M and LAK prepared in Example 1. When PDS and LEV were added to the three-electrode system composed of LAK, the current did not change. However, when PDS was added to the three-electrode system composed of LAK-M, the current moved in the negative direction, and further addition of LEV to the system caused the current to move in the positive direction. This observation indicates that when PDS is added to the system, it extracts electrons from the catalyst, and the further addition of LEV causes LEV to provide electrons to the electron-deficient catalyst, causing LEV to be degraded in the process. It is inferred that the degradation process in which LAK participates is: LAK-M-PDS→e - +LAK-M + -PDS;LAK-M + -PDS+LEV→degradation product+LAK-M-PDS. It can be seen that the presence of the metal amorphous layer can enhance the electron transfer effect and significantly improve the degradation of levofloxacin by the material.

[0054] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A method for preparing an in-situ generated amorphous-crystalline metal attapulgite / carbon composite material, characterized in that: The following steps are involved: S1. Preparation of preliminary activated attapulgite / carbon composite material: Industrial alkali lignin and attapulgite are fully mixed in a mass ratio of 2:1-2:7, and after being evenly mixed, the mixed material is transferred to a vacuum tube furnace and stabilized for 10-60 minutes under the protection of inert gas, and then heated to 550-650°C for pyrolysis for 1-2 hours to obtain a preliminary activated composite material, and then passed through a 200 mesh sieve; S2. Impregnation of metal ions: The composite material obtained in step S1 is immersed in a metal salt solution to obtain an amorphous-crystalline metal attapulgite / carbon composite material; the metal ions in the metal salt solution are Cu, or Cu and Cd, or Ni, or Pb.

2. According to the preparation method according to claim 1, in step S1, the pyrolysis temperature is 600°C and the pyrolysis time is 1 hour.

3. The preparation method according to claim 1, wherein in step S1, the pyrolysis heating rate is 5°C / min-15°C / min.

4. The preparation method according to claim 1, wherein in step S3, the metal salt solution is obtained by dissolving a water-soluble metal salt in water.

5. The amorphous-crystalline metal attapulgite / carbon composite material prepared by the preparation method according to any one of claims 1 to 4.

6. Use of the amorphous-crystalline metal attapulgite / carbon composite material according to claim 5 as a catalyst in PDS-catalyzed degradation of levofloxacin in water.